DAMPAK PHUBBING OLEH GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS MENENGAH - Mustaqim Mustaqim (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study examines the impact of teacher phubbing the act of ignoring social interactions due to smartphone use on students’ academic motivation in Indonesian urban middle schools. Employing a quantitative correlational design, the study surveyed 150 junior and senior high school students across five schools in Jakarta and Bandung, supplemented by unobtrusive classroom observations of 20 teachers. Instruments included an adapted version of the Generic Scale of Phubbing for educational settings, the Academic Motivation Scale (AMS-C 28), and a teacher phubbing behavior checklist. The findings reveal a significant negative correlation between teacher phubbing frequency and students' intrinsic motivation (r = -0.42, p < 0.01). Three main mechanisms were identified: (1) student perception of teacher disinterest, (2) disruption of pedagogical attachment, and (3) decreased classroom engagement. The study contributes theoretically by expanding the construct of digital distraction within educational psychology, and practically by advocating for mindful teaching and digital awareness training for educators. These findings highlight the necessity of embedding digital ethics into 21st-century teaching professionalism to sustain meaningful teacher-student interactions in tech-saturated classrooms.